The historical information in the church archives: Major documentary series for research - Vivas Moreno, Agustín; Pérez Ortiz, Dra. Mª Guadalupe (Documentación de las Ciencias de la Información, 2011)
The present article wants to announce the documentary series that have major interest for the historical investigation in the frame of the ecclesiastic files. For it we will approach first, the different types of ecclesiastic existing files to be extracting from each of them the principal ones and more representative documentary series that integrate his picture of classification. Later, we will observe which are the contents that can be of major usefulness for the historical investigation or that it is the same thing, will show what we can investigate if we take them as a point of reference each of them.
Keywords: ecclesiastic files; documentary series; historical investigation